2020
DOI: 10.4149/gpb_2020008
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of lncRNA PART1 inhibits proliferation, invasion and migration of breast cancer cells and promotes the efficacy of cisplatin in breast cancer cells

Abstract: LncRNAs have proved to be related to the progression of multiple cancers. The present study aimed to investigate the effect of PART1 on the proliferation, invasion and migration of breast cancer cells and the efficacy of cisplatin in these cells. The expression of lncRNA PART1 in tissues and cells were detected by RT-qPCR analysis which was also used to verify the transfection effects. The cell proliferation, invasion and migration of breast cancer cells were respectively analyzed by CCK-8 assay, transwell ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…We further veri ed that MMP13, CP, ICAM1, CDK18 were consistently expressed in the RP3-326I13.1 group by both interference and overexpression, and further indicating that these four mRNA molecules were key mRNAs downstream of RP3-326I13.1. MMP13 had been reported to be involved in the mechanism of cisplatin resistance in some tumors [20][21][22]. Further studies shown that MMP13 could enhance the ability of lung adenocarcinoma cell lines to add value and cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further veri ed that MMP13, CP, ICAM1, CDK18 were consistently expressed in the RP3-326I13.1 group by both interference and overexpression, and further indicating that these four mRNA molecules were key mRNAs downstream of RP3-326I13.1. MMP13 had been reported to be involved in the mechanism of cisplatin resistance in some tumors [20][21][22]. Further studies shown that MMP13 could enhance the ability of lung adenocarcinoma cell lines to add value and cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MMP13 in cisplatin in lung adenocarcinoma was further investigated considering the literatures [20][21][22]. Compared to 0 h, OD450nm absorbance values were signi cantly increased in each group at 24 h (P < 0.001, P < 0.001 and P < 0.001) and 48 h (P < 0.001, P < 0.001, P < 0.001 and P < 0.001).…”
Section: Knock Down Of Hsp90b Decreased the Invasive Ability Of Rp3-326i131mentioning
confidence: 99%